STRATEGI KOMUNIKASI INTERPERSONAL GURU PADA PENDIDIKAN ANAK USIA DINI SELAMA PEMBELAJARAN JARAK JAUH - Purandina, I Putu Yoga (Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
This study aimed to investigate the phenomenon about Teachers’ Interpersonal Communication Strategies in remote teaching during Pandemic COVID-19 at Tunas Mekar Kindergarten Tegaljadi Village and to determine the some resistances found in implementing interpersonal communication strategies by teachers during this Pandemic in Tunas Mekar Tegaljadi Village. It used a qualitative descriptive method using observation sheets and interview guides to teachers and parents. As for the results, first, there was three interpersonal communication strategies used by teacher in remote teaching during Pandimic COVID-19 at TK Tunas Mekar; 1) Communication as Action or One-Way Communication, 2) Communication as Interaction or Two-Way Communication, and 3) Multi-Way Communication or Transaction Communication. Second, there was some problem as a resintance found in implementing those communication strategies the most basic was slow response or feedback from students and parents, children quickly get bored or lose focus, and technical problems regarding internet networks.